2012
DOI: 10.1002/path.4032
|View full text |Cite
|
Sign up to set email alerts
|

Lack of microRNA‐101 causes E‐cadherin functional deregulation through EZH2 up‐regulation in intestinal gastric cancer

Abstract: E-cadherin expression disruption is commonly observed in metastatic epithelial cancers and is a crucial step in gastric cancer (GC) initiation and progression. As aberrant expression of microRNAs often perturb the normal expression/function of pivotal cancer-related genes, we characterized and dissected a pathway that causes E-cadherin dysfunction via loss of microRNA-101 and up-regulation of EZH2 expression in GC. MicroRNA microarray expression profiling and array-CGH were used to reinforce miR-101 involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 57 publications
(79 reference statements)
3
84
0
1
Order By: Relevance
“…In addition, a lower expression of miR-101 is associated with poorer prognosis. A functional analysis has demonstrated that reduced expression of miR-101 promotes cancer proliferation and suppresses apoptosis by directly targeting EZH2 [22,23,24]. Another study showed that overexpression of miR-101 in gastric cancer cell lines inhibits cell proliferation and induces apoptosis in vitro, and inhibits tumor growth in vivo [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a lower expression of miR-101 is associated with poorer prognosis. A functional analysis has demonstrated that reduced expression of miR-101 promotes cancer proliferation and suppresses apoptosis by directly targeting EZH2 [22,23,24]. Another study showed that overexpression of miR-101 in gastric cancer cell lines inhibits cell proliferation and induces apoptosis in vitro, and inhibits tumor growth in vivo [25].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can be measured through high-throughput microarray analysis. In GC, aberrant miRNA expression profiles have been associated with GC progression, prognosis and pathogenesis (16,17) by perturbing the function of target genes (18)(19)(20)(21). For example, miR-148a is significantly downregulated in GC cell lines and tissue (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…It remains vital to define the contributions of other conserved miRNAs in the context of both injury-induced CM proliferation and scar tissue removal. miR-101a is among a suite of highly conserved miRNAs with documented roles in cellular proliferation in the context of cancer, degenerative diseases and, more recently, in myocardial infarction injury to the adult mammalian heart (Carvalho et al, 2012;Pan et al, 2012;Varambally et al, 2008;Wang et al, 2010). Injuryinduced decreases in miR-101a expression stimulated cardiac fibrosis through enhanced fibroblast proliferation but showed no effects on CM proliferation (Pan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%